The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1590/s0103-97332006000300041
|View full text |Cite
|
Sign up to set email alerts
|

Binding energy and photoionization cross-section in GaAs quantum well-wires and quantum dots: magnetic field and hydrostatic pressure effects

Abstract: Using a variational procedure for a hydrogenic donor-impurity we have investigated the influence of an axial magnetic field and hydrostatic pressure in the binding energy and the impurity-related photoionization crosssection in 1D and 0D GaAs low dimensional systems. Our results are given as a function of the radius, the impurity position, the polarization of the photon, the applied magnetic field, the normalized photon energy, and the hydrostatic pressure. In order to describe the Γ-X mixing in the Ga 1−x Al … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(4 citation statements)
references
References 8 publications
1
3
0
Order By: Relevance
“…It is also noted that as the well length increases, the binding energy of the hydrogenic donor impurity tends towards a constant value of about 44.0 meV. This compares favorably with that found by Correa, et al [27]. That is, the binding energy is a nonmonotonic function of the well width and peaks at a relatively small width value.…”
Section: Resultssupporting
confidence: 85%
“…It is also noted that as the well length increases, the binding energy of the hydrogenic donor impurity tends towards a constant value of about 44.0 meV. This compares favorably with that found by Correa, et al [27]. That is, the binding energy is a nonmonotonic function of the well width and peaks at a relatively small width value.…”
Section: Resultssupporting
confidence: 85%
“…7 Sahin 8 has studied the photoionization cross the section of the hydrogenic impurity and intersubband energy level transitions which depend on the size of the quantum well. The binding energy and the dependence of the photoionization cross section on the heterostructure sizes, confining-potential barrier height, applied hydrostatic pressure and magnetic field in the growth direction were investigated by Correa et al 9 who found that the cross section shifts to higher energies when the hydrostatic pressure is increased. Further, Kasapoglu et al 10 have investigated the photoionization cross section in a GaAs/GaAlAs quantum well wire and found that the cross section is affected by the wire size and by the alloy of the barrier.…”
Section: Introductionmentioning
confidence: 99%
“…Works regarding the effects of the hydrostatic pressure on shallow donor impurities have been carried out by Gonzalez et al, Correa and collaborators, and Kasapoglu et al [2][3][4] in quantum well (QW) systems. Morales et al studied the polarization caused by an applied electric field on donor impurities [5] and Morales and Kasapoglu have reported the combined effects of the hydrostatic pressure and electric field on shallow donor impurities in double QW [6,7].…”
Section: Introductionmentioning
confidence: 99%